Evolutionary divergent kinetoplast genome structure and RNA editing patterns in the trypanosomatid Vickermania - Gerasimov, Evgeny S; Afonin, Dmitry A; Škodová-Sveráková, Ingrid; Saura, Andreu; Trusina, Natália; Gahura, Ondřej; Zakharova, Alexandra; Butenko, Anzhelika; Baráth, Peter; Horváth, Anton; Opperdoes, Fred R; Pérez-Morga, David; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
The trypanosomatid flagellates possess in their single mitochondrion a highly complex kinetoplast (k)DNA, which is composed of interlocked circular molecules of two types. Dozens of maxicircles represent a classical mitochondrial genome, and thousands of minicircles encode guide (g)RNAs, which direct the processive and essential uridine insertion/deletion messenger RNA (mRNA) editing of maxicircle transcripts. While the details of kDNA structure and this type of RNA editing are well established, our knowledge mostly relies on a narrow foray of intensely studied human parasites of the genera Leishmania and Trypanosoma. Here, we analyzed kDNA, its expression, and RNA editing of two members of the poorly characterized genus Vickermania with very different cultivation histories. In both Vickermania species, the gRNA-containing heterogeneous large (HL)-circles are atypically large with multiple gRNAs each. Examination of Vickermania spadyakhi HL-circle loci revealed a massive redundancy of gRNAs relative to the editing needs. In comparison, the HL-circle repertoire of extensively cultivated Vickermania ingenoplastis is greatly reduced. It correlates with V. ingenoplastis-specific loss of productive editing of transcripts encoding subunits of respiratory chain complex I and corresponding lack of complex I activity. This loss in a parasite already lacking genes for subunits of complexes III and IV suggests an apparent requirement for its mitochondrial adenosine triphosphate (ATP) synthase to work in reverse to maintain membrane potential. In contrast, V. spadyakhi retains a functional complex I that allows ATP synthase to work in its standard direction.
Keywords: molekulární evoluce; kinetoplast DNA; genom protozoální; RNA editing; RNA Editing; trypanosomatids; Genome, Protozoan; ATP synthase; Vickermania; Evolution, Molecular; DNA, Kinetoplast; Genome, Mitochondrial; editace RNA; genom mitochondriální; kinetoplastová DNA; Trypanosomatina